Tradisi Menghafal Al-Qur’an di Sanggar Qur’an MAN 2 Bukittinggi (Studi Living Qur’an di Sanggar Qur’an MAN 2 Bukittinggi) - Tomi Juliano (Jurnal Cakrawala Akademika, 2024)
Abstract. The tradition of memorizing the Al-Qur'an is one way to maintain the authenticity of the Al-Qur'an. This tradition of memorizing the Al-Qur'an is carried out so that the special qualities of the Al-Qur'an can be maintained among Muslims. Memorizing the Al-Qur'an will be more effective if you are guided well, for example special places such as a Qur'an house, Qur'an studio or similar are provided so that memorizing the Al-Qur'an can be more focused. This research uses a research design observational case study or it could also be called a living Qur'an. Through interviews in this case study, detailed information or information can be obtained regarding the tradition of memorizing the Qur'an at the MAN 2 Bukittinggi Qur'an studio. The data collection techniques used in this research are interviews, observation and documentation with research targets taken using purposive sampling technique, which is a technique for determining samples with certain considerations or special selection. There were 4 informants in this study. The results of this research will reveal how important it is to make the Qur'an a tradition in the Qur'an studio MAN 2 Bukittinggi, as well as the process of memorizing the Qur'an in the studio starting from the registration period until the tahfiz graduation, including several methods that implemented in the Qur'an studio MAN 2 Bukittinggi.